Erythropoietin ameliorates hyperglycemia in type 1-like diabetic rats - Niu HS; Chang CH; Niu CS; Cheng JT; Lee KS (Dove Medical Press, 2016)
Ho-Shan Niu,1 Chin-Hong Chang,2,3 Chiang-Shan Niu,1 Juei-Tang Cheng,3,4 Kung-Shing Lee5–7 1Department of Nursing, Tzu Chi University of Science and Technology, Hualien City, Taiwan, Republic of China; 2Department of Neurosurgery, 3Department of Medical Research, Chi-Mei Medical Center, Yong Kang, Tainan City, Taiwan, Republic of China; 4Institute of Medical Sciences, Chang Jung Christian University, Gueiren, Tainan City, Taiwan, Republic of China; 5Department of Surgery, Division of Neurosurgery, Pingtung Hospital, Pingtung, Taiwan, Republic of China; 6Department of Surgery, Kaohsiung Medical University Chung-Ho Memorial Hospital, Kaohsiung City, Taiwan, Republic of China; 7School of Medicine, Kaohsiung Medical University, Kaohsiung City, Taiwan, Republic of China Background: Erythropoietin (EPO) is widely used in diabetic patients receiving hemodialysis. The role of EPO in glucose homeostasis remains unclear. Therefore, we investigated the effect of EPO on hyperglycemia in rats with type 1-like diabetes.Methods: Rats with streptozotocin-induced type 1-like diabetes (STZ rats) were used to estimate the blood glucose-lowering effects of EPO, and changes in the expression levels of glucose transporter 4 (GLUT4) and the hepatic enzyme phosphoenolpyruvate carboxykinase (PEPCK) were identified by Western blot analysis.Results: EPO attenuated the hyperglycemia in the STZ rats in a dose-dependent manner without altering the hematopoietic parameters, including the hematocrit and number of red blood cells. The involvement of the EPO receptor (EPOR) was identified using EPOR-specific antibodies. In addition, injection of EPO enhanced the glucose utilization, which was assessed using an intravenous glucose tolerance test in rats. However, blood insulin was not changed by EPO in this assay, showing the insulinotropic action of EPO. Moreover, EPO treatment increased the insulin sensitivity. Western blots indicated that the phosphorylation of AMP-activated protein kinase was enhanced by EPO to support the signaling caused by EPOR activation. Furthermore, the decrease in the GLUT4 level in skeletal muscle was reversed by EPO, and the increase in the PEPCK expression in liver was reduced by EPO, as shown in STZ rats.Conclusion: Taken together, the results show that EPO injection may reduce hyperglycemia in diabetic rats through activation of EPO receptors. Therefore, EPO is useful for managing diabetic disorders, particularly hyperglycemia-associated changes. In addition, EPO receptor will be a good target for the development of antihyperglycemic agent(s) in the future. Keywords: erythropoietin, GLUT4, PEPCK, STZ rats